Incorporating real time velocity map image reconstruction into closed-loop coherent control - Rallis, C. E.; Burwitz, T. G.; Andrews, P. R.; Zohrabi Alaei, Mohammad; Averin, R.; De, S.; Bergues, B.; Jochim, Bethany; Voznyuk, A. V.; Gregerson, Neal; Gaire, B.; Znakovskaya, I.; et al. (My University, 2015)
We report techniques developed to utilize three-dimensional momentum information as feedback in adaptive femtosecond control of molecular dynamics. Velocity map imaging is used to obtain the three-dimensional momentum map of the dissociating ions following interaction with a shaped intense ultrafast laser pulse. In order to recover robust feedback information, however, the two-dimensional momentum projection from the detector must be inverted to reconstruct the full three-dimensional momentum of the photofragments. These methods are typically slow or require manual inputs and are therefore accomplished offline after the images have been obtained. Using an algorithm based upon an “onion-peeling” (also known as “back projection”) method, we are able to invert 1040 × 1054 pixel images in under 1 s. This rapid inversion allows the full photofragment momentum to be used as feedback in a closed-loop adaptive control scheme, in which a genetic algorithm tailors an ultrafast laser pulse to optimize a specific outcome. Examples of three-dimensional velocity map image based control applied to strong-field dissociation of CO and O2 are presented.
Keywords: Dissociation; Image sensors; Three dimensional image processing; Cameras; Ionization